Compatibility studies on development of pearl millet flour based pasta - Gull, Amir; Muzaffar, Khalid; Nayik, Gulzar Ahmad; Ganaie, Tariq Ahmad; Kumar, Pradyuman (Journal of Postharvest Technology, 2017)
Convenience and palatability make the pasta more popular worldwide and very recently it is gaining popularity among the common man in  India too. This traditional cereal based food is a result of dough or moisture enriched flour, shaped in various forms. Spaghetti, macaroni and  vermicelli are the popular pasta forms. Normally, this product is high in starch but low in dietary fiber, minerals, vitamins and phenolic  compounds. Increased concern for health consciousness, nutritious pasta products richin fibre and various essential micronutrients having low  glycemic index may be of preference. Pearl millet is an extensively grown tiny millet grain and found rich in dietary fibre and essential  minerals. High polyphenol content of seed coat gives this millet a dark brown tinge. Addition of pearl millet flour to semolina in making the  pasta not only improves the nutritional properties but also found an attractive colour and thus affected the appearance. The extent of tinge  may thus be considered as an indicator of pearl millet addition and reflects the nutritional enhancement. Physical, chemical, cooking  rheological and sensory evaluation was carried out for the developed pasta and found the optimal cooking time lesser than control pasta with  softer texture. Therefore, quality pasta by substituting semolina with pearl millet flour could be developed, which not only enrich the pasta with  various phytochemicals but also give variety to the range of pasta and options to use the millet in value addition.
Keywords: Pearl millet; phytochemicals; semolina; cooking quality; texture and sensory properties